HOLISTIC TEACHING AND THE HOLISTIC THEORY OF THE LAW - Mitrović, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Abstract: Holistic understanding has existed since time immemorial, though without holistic theories of the law. The contemporary development of the theory of the law is characterised by an increased interest of philosophers and scientists in holistic learning as a result of an ever-increasing strengthening of the belief in the existence of a complex web of permeation and interdependence between the world, society, state and the law. All holistic and legal teachings contain one essential shortcoming: the existing and possible holistic links between nature, society, state and the law are static in its substance. They come to life only when legal models are made and examined by computer simulation. Then holism comes to life in the virtual world. This means that for the first time in human history, alongside the real world is being established a new, alternative path or approach to that virtual (metha)world. So far, scientists and jurists have dealt with the real world. Perhaps time has come for them to start exploring the new virtual world and its relationship with the real world. The state and the law are definitely a part of both those worlds.